PRAKTEK TERAPI PENGOBATAN TRADISIONAL MELAYU: SEBUAH SKETSA AWAL - Malki Ahmad Nasir (TEMALI : Jurnal Pembangunan Sosial, 2019)
This paper discusses traditional medicine practiced by Malays. Basically, traditional medicine is indeed inseparable from its environment where humans interact with nature, even their lives depend on basic ingredients found in the surrounding environment. Therefore, to understand the healthy way of life of the community, the study of Malay manuscripts is important because it is a primary source, as found in the texts. For this reason, this paper seeks to present the prescriptions contained in the views of Islam as seen in the Tibb al-Nabawi genre as the right thing in the context of the contribution of the Natural Malay-Archipelago civilization to the outside world, especially in traditional medicine, especially in the text 19th or 20th century Malay texts based on existing texts.